AB0650 Autoantibody Profile in Systemic Sclerosis Associated Pulmonary Hypertension. (10th June 2014) - Sobanski, V.; Nihtyanova, S.; Lynch, B.; Schreiber, B.; Harvey, J.; Handler, C.; Denton, C.; Coghlan, G.
Abstract : Background: Pulmonary hypertension (PH) is a severe complication of systemic sclerosis (SSc), affecting around 10% of patients. A recent meta-analysis showed an overall 3-year survival of 52% 1 . The impact of autoantibody on clinical phenotype of PH-SSc patients is not completely established. Objectives: This study aimed to describe and compare the type of PH and hemodynamic characteristics between different profiles of autoantibody in SSc patients. Methods: 543 patients diagnosed with PH on right heart catheterisation (mean pulmonary arterial pressure mPAP ≥25mmHg) between 1998 and 2012 were retrieved from our local database. Anti-nuclear antibody (ANA) profiles (n=457) were retrieved from clinical immunology records (missing data in 86 patients). Results: The distribution of ANA among SSc-PH patients was as follows: anticentromere antibody (ACA) 35%, anti-topoisomerase I (ATA) 12%, anti-RNA polymerase III (ARA) 6%, anti-U1RNP 5%, anti-U3RNP 4%, anti-PM/Scl 2%, anti-Th/To 2%. Seven percent of patients had multiples specificities or anti-dsDNA or anti-Ro/SSa alone. Twelve percent were ANA positive in immunofluorescence and ENA (extractable nuclear antigen) negative. Four percent were ANA negative. Types of PH in patients with different ANA are presented in Fig. 1. In PAH-SSc patients (n=308), significant differences were found between ANA groups for: age at PAH diagnosis (p<0.001), mPAP (p=0.045), FVC (p<0.001) and DLCO (p<0.001). Patients with ACA, ATA, ENA negative and ANA negative had the highest means of age at PAH diagnosis; patients with anti-U3RNP and anti-PM/Scl had the lowest. Patients with ACA had a higher FVC than ATA and ENA negative patients (p<0.05). Patients with ATA and ENA negative had the lowest DLCO. There was a trend for lower mPAP in ATA than in ANA negative patients (p=0.091). No other significant difference in hemodynamic characteristics was found between PAH-SSc patients. Conclusions: This study provides original data on ANA profile in PH-SSc patients from a large cohort offering quasi-exhaustivity of haemodynamic data. Our data suggests that ANA might provide tools to cluster PH patients in different phenotypes: a phenotype "PAH-like" in ACA, U3RNP, Th-To patients and a phenotype "PH due to lung disease-like" in ATA (ILD), PM/Scl and ARA patients. References: Lefèvre G et al. Survival and prognostic factors in systemic sclerosis-associated pulmonary hypertension: a systematic review and meta-analysis. Arthritis Rheum. 2013;65(9):2412-23 Acknowledgements: Vincent Sobanski has received research grants from Association des Sclérodermiques de France, Société Nationale Française de Médecine Interne, Groupe Pasteur-Mutualité, GSK and Institut Servier. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4495